Correlation between cytological and histopathological diagnosis of non-small cell lung cancer and accuracy of cytology in the diagnosis of lung cancer - Džambas, Jelena; Aleksić, Ivan; Škuletić, Vesna; Cerović, Snežana; Tegeltija, Dragana (Vojnosanitetski pregled, 2022)
Background/Aim. Lung cancer is one of the most common cancer types worldwide. More than 70% of patients are diagnosed with lung cancer in the advanced stages of the disease, with limited therapeutic options based on cytological and histopathological material. The value of cytology in diagnosing and subtyping non-small cell lung cancer (NSCLC) is very important for modern personalized therapies. The aim of this study was to find out the concordance between cytological and histopathological diagnosis of NSCLC and the accuracy, sensitivity, specificity, and the positive and negative predictive value of cytology in diagnosing lung cancer. Methods. A two-year retrospective study included 169 patients with cytological diagnosis of NSCLC, who, at the same time, had small biopsy and surgical specimens for histopathological diagnoses confirmation that were compared with cytological one. Histopathological diagnosis on surgical specimens was the golden standard for evaluation concordance to the cytological diagnosis of NSCLC and evaluation accuracy, specificity, sensitivity, and the positive and negative prognostic value of cytology as a diagnostic method for detecting lung cancer. Results. This study included 129 (76.3%) male and 40 (23.7%) female patients, aged between 39 and 83, with the average of 62.53 ± 7.6. There was no statistically significant difference between the ages of different genders (p = 0.207). The most frequent diagnosis among cytological diagnoses was NSCLC in 99 (58.58%) patients. Concordance between cytological and histopathological diagnoses of surgical specimens was 61.48%. There was no statistically significant difference between cytological diagnoses and histopathological diagnoses of small biopsies specimens (p = 0.856). The sensitivity, specificity, positive and negative prognostic value, and accuracy of cytology as a diagnostic method of lung cancer were 94.98%, 98.60%, 95.72%, 98.35%, and 97.71%, respectively. Conclusion. Cytological diagnosis of NSCLC is accurate, with high sensitivity, specificity, and benefits for patients. Most patients are diagnosed with advanced cancer when there is no surgical therapy option, and the only available diagnostic material is a small biopsy sampled during bronchoscopy.